Diverse Roles and Therapeutic Potentials of Circular RNAs in Urological Cancers - Wang, Song; Ying, Yufan; Ma, Xueyou; Wang, Weiyu; Wang, Xiao; Xie, Liping (Frontiers in Molecular Biosciences, 2021)
Circular RNAs (circRNAs) are a novel class of noncoding RNAs, which are mainly formed as a loop structure at the exons caused by non-canonical splicing, they are much more stable than linear transcripts, recent reports have suggested that the dysregulation of circRNAs is associated with the occurrence and development of diseases, especially various human malignancies. Emerging evidence demonstrated that a large number of circRNAs play a vital role in a series of biological processes such as tumor cell proliferation, migration, drug resistance, and immune escape. Additionally, circRNAs were also reported to be potentially prognostic and diagnostic biomarkers in cancers. In this work, we systematically summarize the biogenesis and characteristics of circRNAs, paying special attention to potential mechanisms and clinical applications of circRNAs in urological cancers, which may help to develop potential therapy targets for urological cancers in the future.